1989
DOI: 10.1002/1097-0142(19890801)64:3<721::aid-cncr2820640326>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Dermatofibrosarcoma protuberans with fibrosarcomatous areas. A clinicopathologic study of nine cases and a comparison with allied tumors

Abstract: Nine cases of dermatofibrosarcoma protuberans with fibrosarcomatous areas (DFSP with FS) were analyzed clinicopathologically, and the findings compared with allied tumors comprising 43 cases of ordinary DFSP, ten of superficial fibrosarcoma (SFS), and 11 of storiform variant of malignant fibrous histiocytoma (SV MFH). All but one case of DFSP with FS developed on the trunk of the body. Eight of the nine patients (89%) had one recurrence with a shorter prerecurrent interval than that of the ordinary DFSP, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(55 citation statements)
references
References 15 publications
3
52
0
Order By: Relevance
“…17 It has been reported that in cases with a fibrosarcomatous area in ordinary dermatofibrosarcoma protuberans or with fibrosarcoma in the recurrent or metastatic lesion, the tumor shows an aggressive clinical course. [18][19][20][21][22][23] By using a microdissection technique, Wang et al 24 detected identical COL1A1-PDGFB fusion transcripts in the two cellular components of dermatofibrosarcoma protuberans with fibrosarcomatous areas. In the present study, we detected COL1A1-PDGFB fusion transcripts in 42 of 57 cases that included 10 dermatofibrosarcoma protuberans with fibrosarcomatous areas, four SAF, three myxoid dermatofibrosarcoma protuberans, and three Bednar tumor.…”
Section: Pdgfb and Pdgfrb Mrna Expressionmentioning
confidence: 99%
“…17 It has been reported that in cases with a fibrosarcomatous area in ordinary dermatofibrosarcoma protuberans or with fibrosarcoma in the recurrent or metastatic lesion, the tumor shows an aggressive clinical course. [18][19][20][21][22][23] By using a microdissection technique, Wang et al 24 detected identical COL1A1-PDGFB fusion transcripts in the two cellular components of dermatofibrosarcoma protuberans with fibrosarcomatous areas. In the present study, we detected COL1A1-PDGFB fusion transcripts in 42 of 57 cases that included 10 dermatofibrosarcoma protuberans with fibrosarcomatous areas, four SAF, three myxoid dermatofibrosarcoma protuberans, and three Bednar tumor.…”
Section: Pdgfb and Pdgfrb Mrna Expressionmentioning
confidence: 99%
“…Fibrosarcoma can arise in DFS, both de novo and in recurrent lesions [9,[26][27][28][29][30][31]. It is characterized by greater cellularity with fascicular architecture and increased mitotic activity ( Figure 5).…”
Section: Fibrosarcomamentioning
confidence: 99%
“…DFSP contains fibrosarcomatous areas appearing as a fascicular pattern and usually plumper cells with more atypia as shown in this case. 6,22) Sarcomatous areas have lower immunoreactivity for CD34 than DFSP. 9) Sarcomatous areas are more commonly encountered in recurrent lesions and are associated with more local recurrence.…”
Section: Discussionmentioning
confidence: 97%